Statistical analysis : with business and economic applications - Chou, Ya-lun (London: Holt, Rinehart and Winston, 1969)
This book is intended for use in either a one semester or two semester course at the undergraduate or the graduate level in statistics for students majoring in Economics and business who had have had only freshman mathematics.
aia 07/09/18
Keywords: Statistics; Business economics; Economic conditions